Discovery of a new potent inhibitor of mushroom tyrosinase (Agaricus bisporus) containing 4-(4-hydroxyphenyl)piperazin-1-yl moiety. Issue 11 (1st June 2020) - De Luca, Laura; Germanò, Maria Paola; Fais, Antonella; Pintus, Francesca; Buemi, Maria Rosa; Vittorio, Serena; Mirabile, Salvatore; Rapisarda, Antonio; Gitto, Rosaria
Graphical abstract: Abstract: Tyrosinase (TYR, EC 1.14.18.1) plays a pivotal role in mammalian melanogenesis and enzymatic browning of plant-derived food. Therefore, tyrosinase inhibitors (TYRIs) can be of interest in cosmetics and pharmaceutical industries as depigmentation compounds as well as anti-browning agents. Starting from 4-benzylpiperidine derivatives that showed good inhibitory properties toward tyrosinase from Agaricus bisporus (TyM), we synthesized a new series of TYRIs named 3-(4-benzyl-1-piperidyl)-1-(4-phenylpiperazin-1-yl)propan-1-one and 2-(4-benzyl-1-piperidyl)-1-(4-phenylpiperazin-1-yl)ethanone derivatives. Among them, compound 4b proved to be the most potent inhibitor (IC50  = 3.80 µM) and it also showed a good antioxidant activity. These new data furnished additional information about the SAR for this class of TYRIs.